2023
DOI: 10.1111/tpj.16387
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in Brachypodium distachyon responses to combined abiotic stresses

Abstract: SUMMARYThe demand for agricultural production is becoming more challenging as climate change increases global temperature and the frequency of extreme weather events. This study examines the phenotypic variation of 149 accessions of Brachypodium distachyon under drought, heat, and the combination of stresses. Heat alone causes the largest amounts of tissue damage while the combination of stresses causes the largest decrease in biomass compared to other treatments. Notably, Bd21‐0, the reference line for B. dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 162 publications
(279 reference statements)
0
1
0
Order By: Relevance
“…These authors further identified the oxidative phosphorylation pathway and alternative oxidase 1 as potentially playing a key role in this stress combination. In the third research paper of the special issue, Ludwig et al (2024) studied phenotypic variation in the response of 149 accessions of Brachypodium to heat, drought, and drought combined with heat. Using GWAS and SNP analyses the authors identified different loci associated with plant responses to stress combination, revealing that these responses are not simply the additive effects of drought and heat, as they differ qualitatively from the responses to drought or heat alone.…”
mentioning
confidence: 99%
“…These authors further identified the oxidative phosphorylation pathway and alternative oxidase 1 as potentially playing a key role in this stress combination. In the third research paper of the special issue, Ludwig et al (2024) studied phenotypic variation in the response of 149 accessions of Brachypodium to heat, drought, and drought combined with heat. Using GWAS and SNP analyses the authors identified different loci associated with plant responses to stress combination, revealing that these responses are not simply the additive effects of drought and heat, as they differ qualitatively from the responses to drought or heat alone.…”
mentioning
confidence: 99%